CRIMINAL RESPONSIBILITIES OF STATE-OWNED ENTERPRISES (BUMN) IN INDONESIA AS THE PERPETRATORS OF MONEY LAUNDERING THAT ORIGINATED FROM CORRUPTION - Fakhri Arindra Zaki; Toetik Rahayuningsih (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The existence of State-Owned Enterprises (BUMN) in Indonesia has the objective to manage the fields related to the lives of many people. However, in its development there have been efforts to enrich themselves or groups (in BUMN), such as the case of money laundering and corruption that inflict a financial lost to the country. Aim: For this reason, this research is structured with the aim of analyzing the criminal liability of State-Owned Enterprises (BUMN) in Indonesia as the perpetrators of money laundering that originate from corruption. Method: This type of research is legal research or normative research, which is accompanied by the use of three approaches namely the legislative approach (statute approach), concept approach (conceptual approach), and case approach (case approach). Result: The results of the study through the analysis of two decisions namely Decision of the Supreme Court of the Republic of Indonesia Number 787K/Pid.Sus/2014) and Decision The Supreme Court of the Republic of Indonesia Number 1616K/Pid.Sus/2013) which stated that the judge has decided the case of money laundering that comes from corruption. The two decisions stated that the suspect concerned was proven guilty of committing a criminal act of corruption which was carried out jointly. Conclusion: Therefore, it can be concluded that the form of criminal liability in each corruption case of a State-Owned Enterprise (BUMN) continues to be processed in accordance with applicable laws and regulations, where the decision is then weighed and determined by the Supreme Court.